Fair inheritance taxation in the presence of tax planning - Matthias Wrede (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2013)
This paper presents an analysis of the extent to which tax planning affects the level of the inheritance tax rate that is perceived to be fair. In a factorial survey conducted in Germany, tax planning was found to increase the fair tax rate by approximately 4 percentage points. The fair tax rate is determined by not only the size of the bequest, the relationship of the heir to the bequeather, and the type of bequest, but also by the perceived intentions of the bequeather. Families with pro-social motives should be taxed less than those without pro-social motives. The analysis described in this paper finds support in optimal tax theory. To this end, a simple model was developed that shows that taxation should not prevent individuals with warm-glow-of-giving motives from contributing substantially more to the social good than individuals who do not share these motives.
Keywords: H21; H24; H26; 330; tax planning; inheritance tax; fair taxation; warm glow of giving